Penyisihan TSS pada Air Limbah Sawit Di Dalam Flat-Fotobioreaktor Menggunakan Chlorella sp. Yang Diimmobilisasi - Lidya Anggraini; Shinta Elystia; Sri Rezeki Muria (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
High production of palm oil contributes to the high waste water produced. This is because the high water consumption during the production process is about 5 m3 per processing of one ton of fruit palm. The palm oil mill is an important concern because it contains organic materials, tannin compounds and high soluble solids. So it takes an environmentally friendly processing to eliminate pollutants so as not to cause environmental damage. Therefore, in this research, the effluent treatment using Chlorella sp. which is immobilized to exclude TSS parameters. Cell immobilization process is done by using calcium alginate as a polymer to form beads. In order to obtain stable and high efficiency beads, variations of Na-alginate concentration (4%, 6%, 8%) and contact time (1, 3, 5, 7 days) are obtained. Based on the result of the research, it is found that the most stable bead is made of 8% Na-alginate with a removal efficiency of 35.3-76% within seven days.Keywords: Chlorella sp, COD, Contact Time, Na-alginate, Palm Oil Mill Effluent, Total Nitrogen, Total Suspended Solid.